2010
DOI: 10.1111/j.1095-8312.2010.01373.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA and nuclear microsatellites reveal high diversity and genetic structure in an avian top predator, the white-tailed sea eagle, in central Europe

Abstract: We analysed 123 white-tailed sea eagles (Haliaeetus albicilla) from (primarily central) Europe with respect to variability and differentiation based on 499 bp of the mitochondrial control region and genotypes at seven unlinked nuclear microsatellites. Variability was high (overall expected heterozygosity, haplotype and nucleotide diversity being 0.70, 0.764 and 0.00698, respectively) and both marker systems showed a subdivision into two main genetic clusters (microsatellites) or haplogroups (mtDNA). In line wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 39 publications
2
48
0
1
Order By: Relevance
“…Nevertheless, the species is philopatric, as showed both by mark-resight data (Helander 2003, Helander & Stjernberg 2003, Struwe-Juhl & Grünkorn 2007, Whitfield et al 2009a) and the presence of genetic structure at wide geographical range inferred from microsatellite data (Hailer et al 2007, Honnen et al 2010, Nemesházi et al 2016. Moreover, the Carpathian Basin population maintains a local, unique mitochondrial haplotype as well (Honnen et al 2010, Nemesházi et al 2016. Similar contradictions of fine-scale spatial genetic and mark-resight data were reported in a lesser kestrel (Falco naumanni) population (Alcaide et al 2009), where the authors concluded, that rare occurrence of long-distance dispersal events overrode the genetic structure expected in the otherwise philopatric population.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Nevertheless, the species is philopatric, as showed both by mark-resight data (Helander 2003, Helander & Stjernberg 2003, Struwe-Juhl & Grünkorn 2007, Whitfield et al 2009a) and the presence of genetic structure at wide geographical range inferred from microsatellite data (Hailer et al 2007, Honnen et al 2010, Nemesházi et al 2016. Moreover, the Carpathian Basin population maintains a local, unique mitochondrial haplotype as well (Honnen et al 2010, Nemesházi et al 2016. Similar contradictions of fine-scale spatial genetic and mark-resight data were reported in a lesser kestrel (Falco naumanni) population (Alcaide et al 2009), where the authors concluded, that rare occurrence of long-distance dispersal events overrode the genetic structure expected in the otherwise philopatric population.…”
Section: Discussionmentioning
confidence: 84%
“…When we analysed females and males separately, similar lack of fine-scale genetic structure was found, with even the slope ln(dist) being nonsignificant. Nevertheless, the species is philopatric, as showed both by mark-resight data (Helander 2003, Helander & Stjernberg 2003, Struwe-Juhl & Grünkorn 2007, Whitfield et al 2009a) and the presence of genetic structure at wide geographical range inferred from microsatellite data (Hailer et al 2007, Honnen et al 2010, Nemesházi et al 2016. Moreover, the Carpathian Basin population maintains a local, unique mitochondrial haplotype as well (Honnen et al 2010, Nemesházi et al 2016.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…For comparison, data from recent phylogeographic studies of White-tailed Eagles (Hailer et al, 2006(Hailer et al, , 2007Honnen et al, 2010;Langguth et al, 2013;Ponnikas et al, 2013) were used, plus the sequence of a Steller's Sea Eagle (GenBank accession AM156946). Because no mtDNA control region samples from Bald Eagles were available on GenBank, we also sequenced 12 Bald Eagle nestlings from northern Wisconsin, each from a different nest.…”
Section: Lab Proceduresmentioning
confidence: 99%
“…Since the publication of Fleischer et al (2000), extensive studies have been conducted on the phylogeography of the White-tailed Eagle, examining the highly variable mtDNA control region (Hailer et al, 2006(Hailer et al, , 2007Honnen et al, 2010;Langguth et al, 2013;Ponnikas et al, 2013 Molecular Phylogenetics and Evolution 83 (2015) [40][41][42][43] Contents lists available at ScienceDirect Molecular Phylogenetics and Evolution j o u r n a l h o m e p a g e : w w w . e l s e v i e r .…”
Section: Introductionmentioning
confidence: 99%